2018
DOI: 10.3892/etm.2018.6763
|View full text |Cite
|
Sign up to set email alerts
|

Human umbilical cord‑derived mesenchymal stem cells ameliorate the enteropathy of food allergies in mice

Abstract: Food allergy prevalence has steadily increased worldwide over the past decades and immunotherapeutic treatment strategies are gaining attention. Human umbilical cord-derived mesenchymal stem cells (hUC-MSCs) exhibit similar immune regulatory properties to bone marrow-derived MSCs. hUC-MCSs can be prepared with fewer ethical constraints and are potential candidates for allergic disorder therapies. The current study aimed to investigate potential antiallergic properties of hUC-MSCs in mice with ovalbumin (OVA)-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…A number of studies have further demonstrated the beneficial effect of hUCMSCs on intestinal microbiota in a variety of diseases. hUCMSCs were found to facilitate the re-establishment of the intestinal microbiota in food allergy induced by ovalbumin (Yan et al 2018 ). Additionally, hUCMSCs were reported to exert protection against experimental colitis through CD5 + B regulatory cells (Chao et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have further demonstrated the beneficial effect of hUCMSCs on intestinal microbiota in a variety of diseases. hUCMSCs were found to facilitate the re-establishment of the intestinal microbiota in food allergy induced by ovalbumin (Yan et al 2018 ). Additionally, hUCMSCs were reported to exert protection against experimental colitis through CD5 + B regulatory cells (Chao et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The AL asthma protection associated with increased Muribaculaceae (previously called S24-7 47 ) and other Bacteroides species is consistent with their critical roles in early life immunological development. [48][49][50] Muribaculaceae have been associated with alleviation of allergic lung inflammation 51 food allergy 52,53 and with type 1 diabetes protection. 54 Our observations pertaining to Parasutterella are consistent with beneficial metabolic roles of these species.…”
Section: Discussionmentioning
confidence: 99%
“…The results suggested that the soluble factors secreted by MSCs play a major role in regulating immunologic function in the food allergy model. In the study of human umbilical cord-derived MSCs in the food allergy model, allergic symptoms and IL-4, TNF-α mRNA levels, inflammatory cells, and goblet cells in the colon were decreased by MSCs and MSC-CM [ 39 ]. Similar findings were presented in other allergic disease models.…”
Section: Discussionmentioning
confidence: 99%
“…MSCs significantly reversed the higher levels of OVA-induced IL-4 and TNF-α mRNA expressed in the OVA. Treatment with MSC-CM by oral gavage partially restored the gut microbiota and goblet cells as well as commensal bacteria in the gut [ 39 ].…”
Section: Discussionmentioning
confidence: 99%